Improving Learning Outcomes by Using Image Media in Elementary School Students - Safiuddin Safiuddin; Muh Nur Intan Ode; Irman Matje; Faslia Faslia; Krisnawati Krisnawati (Jurnal Wawasan Sarjana, 2023)
The purpose of this study was to describe the use of media images to improve student learning outcomes in class VI on social studies subjects. This research is a class action research containing 2 cycles. Each cycle is 2 meetings. Data analysis techniques using test techniques, interviews, and observation. Data collection techniques in this study are observation, interviews, documentation and tests. In the results of class action research and discussions carried out on the level of completeness of learning outcomes from cycle I to cycle II was 54.54% to 86.36%. Therefore, in cycle II it increased by 31.82%. And the average student learning outcomes from cycle I to cycle II is 67.95 to 71.21. This has increased by 3.32. The use of media images can increase teacher activity in the learning process. This can be obtained in the percentage on the teacher's observation sheet which has increased from cycle I to cycle II. In cycle I, a percentage of 69.04% was obtained and in cycle II, a percentage was obtained as much as 80.75%. In this study, the use of media images can improve the learning outcomes of fourth grade students in social studies at Public Elementary School 1 Kaobula.